Macrophage variance: investigating how macrophage origin influences responses to soluble and physical cues with immortalized vs. primary cells in 2D and 3D culture - Graf, Jodi; Bomb, Kartik; Trautmann-Rodriguez, Michael; Jarai, Bader M.; Gill, Nicole; Kloxin, April M.; Fromen, Catherine A. (Frontiers in Biomaterials Science, 2024)
Macrophages are phagocytic innate immune cells capable of phenotypical switching in response to the local microenvironment. Studies often use either primary macrophages or immortalized cell lines for hypothesis testing, therapeutic assessment, and biomaterial evaluation without carefully considering the potential effects of cell source and tissue of origin, which strongly influence macrophage response. Surprisingly, limited information is available about how, under similar stimuli, immortalized cell lines and primary cells respond in both phenotypical and functional changes. To address this need, in this work, we cultured immortalized macrophage cell lines derived from different origins (i.e., blood, lung, peritoneal) to understand and compare macrophage phenotypical responses, including polarization and plasticity, morphological changes, and phagocytic functionalities of different cell lines, as well as compared primary macrophages extracted from peritoneal and bone marrow to their immortalized cell line counterparts. We found significant differences in baseline expression of different markers (e.g., CD86, MHCII, CD206, and EGR2) amongst different cell lines, which further influence both polarization and repolarization of the cells, in addition to their phagocytic functionality. Additionally, we observed that, while RAW 264.7 cells behave similarly to the primary bone marrow-derived macrophages, there are noticeable phenotypical and functional differences in cell line (IC-21) and primary peritoneal macrophages, highlighting tissue-specific differences in macrophage response amongst cell lines and primary cells. Moving to 3D culture in well-defined biomaterials, blood-derived primary and cell line macrophages were encapsulated within hydrogel-based synthetic extracellular matrices and their polarization profiles and cell morphologies were compared. Macrophages exhibited less pronounced polarization during 3D culture in these compliant, soft materials compared to 2D culture on rigid, tissue culture plastic plates. Overall, our findings highlight origin-specific differences in macrophage response, and therefore, careful considerations must be made to identify the appropriate cell source for the application of interest.